Household chores and leisure activities of married couples in a rural community. - Palmares, Jesry T (1994.)
This is a study on the household chores and leisure activities of married couples in a rural community. The study sought to: 1. Identify the common household chores as well as the common leisure activities performed by husbands and wives. 2. Identify the household chores and the leisure activities performed exclusively by husbands and those performed exclusively by the wives. 3. Analyze the nature of gender differentiation in the performance of household chores and leisure activities of married couples. Based on the findings it was found out that the household chores of married couples in Barangay Malag-it Peque{ogon}o, Passi, were: feeding the animals, gathering firewood, cooking, babysitting and telling stories to kids. Household chores done exclusively by the wives were: washing clothes, cleaning the house, and tutoring the kids. Getting water was a household chore done exclusively by the husbands., As to the nature of gender differentiation in the performance of household chores, it was found out that household activities that require much physical strength were performed by the husbands while those that require less were performed by the wives. Furthermore, as in most rural settings, wives perform more household chores than the husbands. Meanwhile, the common leisure activities of married couples were: listening to the radio, playing with kids, and reading. Leisure activities done exclusively by husbands were: tending the rooster, cockfighting, playing cards, playing basketball, and watching movies. On the other hand, leisure activities done exclusively by the wives were: reading the Bible, playing bingo, manicuring, and chatting with friends. Based on the nature of these activities, it was concluded that some household chores and leisure activities were gender-related. Regarding the nature of gender differentiation in the performance of leisure activities, the study found out that: 1) wives tend to engage more in leisure activities within their homes than the husbands, 2)husbands tend to engage more in group leisure activities than the wives, and 3) husbands tend to engage more in leisure activities that require money than the wives. Finally, pattern was observed in the performance of household chores and leisure activities of husbands and wives. Most husbands either attend to their respective jobs or help their wives in doing household chores first and later engage in leisure activities and then perform household chores again.
Thesis (Undergraduate, Bachelor of Arts in History-Community Development) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Maried Couples -- Rural Community